Adaptation of temperate seagrass to Arctic light relies on seasonal acclimatization of carbon capture and metabolism - Jueterbock, Alexander; Duarte, Bernardo; Coyer, James; Olsen, Jeanine L.; Kopp, Martina Elisabeth Luise; Smolina, Irina Vladimirovna; Arnaud-Haond, Sophie; Hu, Zi-Min; Hoarau, Galice Guillaume (Frontiers in Plant Science, 2021)
publishedVersion